2013
DOI: 10.1186/1741-7015-11-29
|View full text |Cite
|
Sign up to set email alerts
|

Paternal obesity is associated with IGF2hypomethylation in newborns: results from a Newborn Epigenetics Study (NEST) cohort

Abstract: BackgroundData from epidemiological and animal model studies suggest that nutrition during pregnancy may affect the health status of subsequent generations. These transgenerational effects are now being explained by disruptions at the level of the epigenetic machinery. Besides in vitro environmental exposures, the possible impact on the reprogramming of methylation profiles at imprinted genes at a much earlier time point, such as during spermatogenesis or oogenesis, has not previously been considered. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
218
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 304 publications
(237 citation statements)
references
References 59 publications
7
218
1
3
Order By: Relevance
“…Human and animal data suggests that not only maternal health and diet might be of importance for the offspring; there are also indications that the paternal contribution to methylation of imprinted genes and phenotype should be taken into account 73 .…”
Section: Longitudinal Studiesmentioning
confidence: 99%
“…Human and animal data suggests that not only maternal health and diet might be of importance for the offspring; there are also indications that the paternal contribution to methylation of imprinted genes and phenotype should be taken into account 73 .…”
Section: Longitudinal Studiesmentioning
confidence: 99%
“…Evidence is emerging from both animal [53] and human [54] studies that paternal diet can also influence offspring development and health. The former study investigated the effects of male rats fed high-fat diets that led to obesity.…”
Section: Paternal Contributionmentioning
confidence: 99%
“…But, surprisingly, the weight gain also seemed to affect the rats' daughters: the female offspring had trouble controlling their insulin levels despite being on a normal diet. And a study published in 2013 showed that children with obese fathers had less methylation on a particular region of the IGF2 gene than children who were born to lean fathers 14 .…”
Section: Family Heirloomsmentioning
confidence: 99%